An Investigation of Students’ Difficulties in Statistics Learning on Online Based Learning at Universitas Terbuka Taiwan - Ramadoni, Ramadoni; Hafiz, Muhammad (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2022)
This study aims to determine the students’ difficulties in online learning. Online learning is one solution offered by several parties such as the government, universities, and teachers. However, this has not been fully able to help students understand the statistics well. This study investigates students’ difficulties in terms of topics, learning processes, and assignments. The students have taken statistics courses for one semester. The data collection techniques with open questionnaires via google Forms and online interviews. The number of participants for open questionnaires was 25 students and 6 students were taken to be interviewed. Based on the questionnaires and interviews conducted with students, the results of the study are that students still have difficulty in understanding the material itself because of complicated calculations, complicated formulas, and Unrealistic. While the difficulties of students in online learning are limited time, network problems, explanations and examples of questions are not written in detail in online learning, the strategies used in online learning make some students negligent in learning, and the number of online meetings is still lacking, online learning can be helpful but not maximized. Moreover, students’ difficulties with assignments such as the formula are very much, the book has several errors, students do not understand the stages in solving problems, difficulty in determining the symbols used in the story problem, difficulty in calculating it, difficulty in imagining the application of the formula into real life. The recommendation from this study is the statistics teacher can choose the appropriate learning model for statistics courses. Keywords: Students’ Difficulties, Statistics Learning, Online Learning